Mitigation of carrier trapping effects on carrier lifetime measurements with continuous-wave laser illumination for Pb-based metal halide perovskite materials - Lobo, Ntumba; Matt, Gebhard; Osvet, Andres; Shrestha, Shreetu; Kanak, Andrii; Fochuk, Petro; Brabec, Christoph; Kato, Masashi (Journal of Applied Physics, 2024)
We investigated the impact of carrier trapping on the carrier lifetime of metal halide perovskite materials, which are key to solar cell production. We examined NH3CH3PbI3 (MAPbI3), NH3CH3PbBr3 (MAPbBr3), and CsPbBr3 using continuous-wave (CW) laser illumination during microwave photoconductivity decay (μ-PCD) measurements. Traditional pulsed light excitation falls short of mirroring solar cell operating conditions, owing to carrier trapping. Implementing CW laser illumination provides a more accurate estimation of the carrier lifetimes under operational conditions. With an increased photon flux from the CW laser, the μ-PCD decay curves changed, indicating reduced recombination via traps. The experiments revealed extended carrier lifetimes under continuous light for the MAPbI3 polycrystal. This suggests that CW lasers can mitigate trapping effects on carrier lifetime measurements. For the other samples, carrier trapping had a negligible effect on the measured carrier lifetimes. We believe that these findings will aid in the design of perovskite-based devices.
CRIS-Team Scopus Importer:2024-05-03